Metamaterial springs for low-frequency vibration isolation - Wenlong Liu; Lingling Wu; Junming Zhang; Jingbo Sun; Ji Zhou (Journal of Materiomics)
Metadevices have emerged as a new element or system in recent years, from optics to mechanical science, showing superior performance and powerful application potential. In this study, a mechanical metadevice that capable of low-frequency vibration isolation, which is called metamaterial springs or metasprings, is proposed. Meanwhile, a modular design method is reported to obtain the customizable quasi-zero stiffness characteristic of the designed metaspring. As proof-of-concept, we demonstrate, both in simulations and experiments, the quasi-zero stiffness characteristics of the proposed metasprings using 3D-printed experimental specimens. Moreover, the low-frequency vibration isolation properties of the proposed metasprings is demonstrated both in vibration tests and automotive vibration tests. This work provides a new mechanical metadevice, that is, metasprings for low-frequency vibration isolation, as well as a modular design method for designing metasprings, which may revolutionize vibration isolation devices in the field of low-frequency vibration isolation.